The Effects of Eccentric Strength Training on Flexibility and Strength in Healthy Samples and Laboratory Settings: A Systematic Review - Vetter, Sebastian; Schleichardt, Axel; Köhler, Hans-Peter; Witt, Maren (Frontiers in Physiology, 2022)
Background: The risk of future injury appears to be influenced by agonist fascicle length (FL), joint range of motion (ROM) and eccentric strength. Biomechanical observations of the torque-angle-relationship further reveal a strong dependence on these factors. In practice, a longer FL improves sprinting performance and lowers injury risk. Classical stretching is a popular and evidenced-based training for ROM but does not have any effects on FL and injury risk. However, recent studies show that eccentric-only training (ECC) improves both flexibility and strength, and effectively lowers risk of injury. Objectives: To review the evidence on benefits of ECC for flexibility and strength. Methods: COCHRANE, PUBMED, SCOPUS, SPOLIT, and SPONET were searched for laboratory trials that compare ECC to at least one control group (CG). Studies were eligible if they examined both strength and flexibility metrics in a healthy sample (<65y) and met criteria for controlled or randomized clinical trials (CCT, RCT). 18 studies have been included and successfully rated using the PEDro scale. Results: 16 of 18 studies show strong evidence of strength and flexibility enhancements for the lower limb. While improvements between ECC and concentric training (CONC) were similar for eccentric (+19 ± 10% vs. +19 ± 11%) and isometric strength (+16 ± 10% vs. +13 ± 6%), CONC showed larger improvements for concentric strength (+9 ± 6% vs. +16 ± 7%). While for ROM ECC showed improvements (+9 ± 7%), no results could be found for CONC. The overall effectiveness of ECC seems to be higher than of CONC. Conclusion: There is clear evidence that ECC is an important predictor for changes in muscle architecture, leading to both flexibility and strength improvements for the lower limb. Due to limited data no shoulder study could be included. Further research is needed for the upper body joints with a focus on functional and structural adaptions.